Researching Literary Tourism: A Handbook for Students and Supervisors - Jasna Potočnik Topler, Jasna Potočnik Topler; Baleiro, Rita; Capecchi, Giovanni; Mansfield, Charles (University of Maribor Press, 2024)
The textbook Researching Literary Tourism: A Handbook for Students and Supervisors is intended for students and supervisors, offering basic knowledge and guidelines for successful research in literary tourism. The textbook begins with an introduction to basic terms and concepts, enabling students to understand the context and the importance of literary tourism. The authors provide specific examples, guidelines, and propose qualitative and quantitative methods for research, aiming to encourage students to plan their own studies and engage in field research. The goal is to develop key research skills in the field of literary tourism, such as data collection, analysis, critical thinking, and writing. Researching the interdisciplinary field of literary tourism, which has certain special characteristics, can significantly contribute to the development of tourist destinations, the promotion of cultural heritage, and sustainable economic development.